Binding of cyclin-dependent kinases to ORC and Cdc6p regulates the chromosome replication cycle - Weinreich, Michael (The National Academy of Sciences, 2001)
Cdc6p and the origin recognition complex (ORC) are essential for assembly of a pre-replicative complex (preRC) at origins of replication, before the initiation of DNA synthesis. In the absence of Cdc6p, cells fail to initiate DNA replication and undergo a “reductional” mitosis, in which the unreplicated chromosomes are randomly segregated to the spindle poles. We show here that the cells harboring a mutation in the essential Cdc6p Walker A-box arrest in late mitosis, probably at anaphase. This cell cycle block requires either the three Cdc28p phosphorylation sites within the N terminus of Cdc6p or a short region (aa 8–17) that contains a Cy (Cyclin) interaction sequence. These same two Cdc6p mutants that allow a reductional mitosis are defective in binding Cdc28p kinase. In addition to Cdc6p, ORC also binds to cyclin-dependent kinases (CDKs). Interestingly, Sic1p, a CDK inhibitor protein, blocked the S phase-specific Cdc28p-Clb5p kinase from interacting with ORC, but did not prevent the G(1)-specific Cdc28p-Cln2p kinase–ORC interaction. We suggest that ORC, Cdc6p, and Sic1p bind to different CDKs in a cell cycle-dependent manner to temporally regulate events that (i) allow preRC formation after mitosis, (ii) prevent mitosis before DNA replication can occur, and (iii) promote initiation of DNA replication.